Efecto de los sistemas productivos de café (coffea arábica. L) orgánico y convencional... - Huamán Saldaña, María Aidely (2015)
The present investigation of productive systems effect of organic coffee and conventional soil on the macro invertebrates in San Vicente hamlet of Jepelacio district, Moyobamba Province and San Martin Department, it is known that according to the survey to learn about the features of the management of the productive systems of conventional and organic coffee, according to the cultural work associated with the cultivation of coffee fertilization in the organic coffee is performed through the use of organic fertilizers such as compost while in the coffee used conventional chemical fertilizers as the compo master and follares; on the other hand in the work of conservation soil organic producers and used conventional contour planting and live barriers this emphasizes that both types of producers perform soil conservation practices which are very substantial to retain the soil and minimize the impact of environment agriculture. In addition to learn about the biodiversity of the productive systems of conventional and organic coffee is determined by the use of the index specifies where wealth is identified that the greater presence of taxa is located in the organic coffee represented by 13 taxa at the level of order and the results for conventional coffee showed a total of 1 O taxa, he re is evidence that the effect is the mishandling of the conventional coffee farms on the survival of the various bodies that inhabit it. Finally according to the chemical analysis of soils for the productive system of conventional coffee, had high levels of mineral due to applications of chemical fertilizers programed. Key words: organic coffee; environment agriculture